2018
DOI: 10.1016/j.bcp.2018.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic modulation of cAMP levels by the contraceptive nomegestrol acetate. Impact on P-glycoprotein expression and activity in hepatic cells

Abstract: ABC transporters are key players in drug excretion with alterations in their expression and activity by therapeutic agents potentially leading to drug-drug interactions. The interaction potential of nomegestrol acetate (NMGA), a synthetic progestogen increasingly used as oral contraceptive, had never been explored. In this work we evaluated (1) the effect of NMGA on ABC transporters in the human hepatic cell line HepG2 and (2) the underlying molecular mechanism. NMGA (5, 50 and 500 nM) increased P-glycoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Then, they were incubated with culture medium alone (control group) or culture medium containing 50 µM adenosine (adenosine group) for 15 minutes. Immediately afterwards, cells were washed with PBS and lysed in HCl (0.1 M, 20 min) at room temperature in order to stop phosphodiesterase activity and stabilize the released cAMP 67,68 . Finally, cAMP was quantified using the cAMP Select ELISA kit (Cayman Chemical, Ann Arbor, USA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Then, they were incubated with culture medium alone (control group) or culture medium containing 50 µM adenosine (adenosine group) for 15 minutes. Immediately afterwards, cells were washed with PBS and lysed in HCl (0.1 M, 20 min) at room temperature in order to stop phosphodiesterase activity and stabilize the released cAMP 67,68 . Finally, cAMP was quantified using the cAMP Select ELISA kit (Cayman Chemical, Ann Arbor, USA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decades, the membrane progesterone receptors (mPRα) and progesterone receptor membrane component 1 (PRGMC1) have been considered as possible participants in MDR. It has been recently shown that mPRα activated by progestin nomegestrole acetate (NMGA) caused Pgp mRNA up-regulation in HepG2 and Huh7 cells [ 105 ]. This was the first mention of mPR as a regulator of the drug efflux linked to MDR.…”
Section: Progestins As Chemosensitizers Possible Targetsmentioning
confidence: 99%